Meg of Mystery Mountain - North, Grace May, 1876-1960 (Salt Lake City, UT : Project Gutenberg, 2013)
"Meg of Mystery Mountain" by Grace May North is a novel written in the early 20th century. The story centers around a group of girls, primarily focusing on Jane Abbott, a selfish and beautiful young woman who struggles with the realities of her family's financial downfall. As they transition from the comforts of the Highacres Seminary to the less glamorous life in the mountains, the narrative explores themes of personal growth, friendship, and the clash between social status and true character. At the start of the book, we meet Jane Abbott and her friends as they depart the prestigious Highacres Seminary. Jane grapples with her pride and vanity, feeling mortified at the thought of returning to her family's modest home in Edgemere after their father's financial troubles. The dynamics of her friendships are tested when she initially expresses disinterest in supporting her ailing brother, Dan, who has worked hard to ensure she could enjoy her time at the seminary. Despite her self-absorbed nature, Jane eventually decides to accompany Dan on a journey to their father's cabin in the mountains, setting the stage for her potential character development as they face life's challenges together. (This is an automatically generated summary.)
Release date is 2013-02-04
E-text prepared by Stephen Hutcheson, Rod Crawford, Dave Morgan, and the Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Detective and mystery stories; Friendship -- Juvenile fiction; Rocky Mountains -- Juvenile fiction; Teenagers -- Juvenile fiction